Paradigm lost, paradigm gained?: Building a democratised political economy. Issue 3 (December 2014) - Lawrence, Mathew
<x xml:space="preserve">Abstract</x> Mathew Lawrence urges progressives to raise their ambitions above a rearguard defence of 20th century social democracy, and instead take the first steps towards a gradual and broad‐based democratisation of the UK's political economy.